Gender differences in well-being among people living with non-communicable disease: The influence of social capital and grants - Aaron Kobina Christian; Daniel Egerson; Sandra Boatemaa Kushitor (PLoS ONE, 2025)
Background This study explores how non-communicable diseases (NCDs), social capital, and government grants (social grants) influence subjective well-being (SWB) among individuals aged 40 and older in rural South Africa. Understanding gender differences in these relationships provides insights for improving public health interventions in resource-constrained settings. Methods Data from 2,432 participants in the HAALSI Wave 3 study were analyzed to examine the predictors of SWB using regression models. Key covariates included age, education, marital status, employment, wealth, religion, social capital, and social grants. Interaction effects between NCDs, social capital, and social grants were evaluated, with gender-stratified analyses to explore disparities. SWB scores were computed, and statistical significance was assessed at various thresholds. Results About a third of the sample had hypertension (58%), one-fifth had diabetes (20%), and nearly two-fifths had depression (36%). Having an NCD) was significantly associated with lower subjective wellbeing (β = −0.855, p < 0.001), with a slightly stronger negative effect observed among women than men. Older age (particularly 80+), and lower education were also associated with reduced wellbeing. Social capital did not moderate the negative impact of NCDs, as individuals with NCDs reported similarly low wellbeing regardless of high or low social capital. However, access to social grants showed some buffering effect: individuals with NCDs and high social grants reported better wellbeing outcomes compared to those with NCDs and low grants, particularly among males. Health insurance coverage was positively associated with wellbeing across all groups. Conclusions These findings suggest that while NCDs significantly reduce wellbeing, social capital alone may not mitigate this burden, whereas targeted material support through grants may offer partial protection, particularly for men. We recommend the development of NCD financing strategies within the public healthcare funding schemes.